The cerebellar fastigial nucleus contributes to CO(2)-H(+) ventilatory sensitivity in awake goats - Martino, P.F. (2007)
The purpose of this study was to test the hypothesis that an intact cerebellar fastigial nucleus (CFN) is an important determinant of CO(2)-H(+) sensitivity during wakefulness. Bilateral, stainless steel microtubules were implanted into the CFN (N = 9) for injection (0.5–10 μl) of the neurotoxin ibotenic acid. Two or more weeks after implantation of the microtubules, eupneic breathing and CO(2)-H(+) sensitivity did not differ significantly (P > 0.10) from pre-implantation conditions. Injection of ibotenic acid (50 mM) did not significantly alter eupneic Pa(CO(2)) (P > 0.10). The coefficient of variation of eupneic Pa(CO(2)) was 4.0±0.6 and 3.7±0.4% over the 2 weeks before and after the lesion, respectively. CO(2)-H(+) sensitivity expressed as inspired ventilation/Pa(CO(2)) decreased from 2.15±0.17 pre-lesion to 1.58±0.26 l/(min mmHg) 3–6 days post-lesion (P < 0.02, −27%). There was no significant (P > 0.10) recovery of sensitivity between 7 and 10 days post-lesion. The lesion also increased (P < 0.05) the day-to-day variability of this index by nearly 100%. When CO(2) sensitivity was expressed as elevated inspired CO(2)/room air V̇(I), values at 7%, but not 3 and 5% inspired CO(2), were reduced and more variable (P < 0.05) after the ibotenic acid injections. We conclude that during wakefulness, the CFN contributes relatively more to overall ventilatory drive at high relative to low levels of hypercapnia.